Contribution of Convexal Subarachnoid Hemorrhage to Disease Progression in Cerebral Amyloid Angiopathy. Issue 6 (June 2015) - Beitzke, Markus; Enzinger, Christian; Wünsch, Gerit; Asslaber, Martin; Gattringer, Thomas; Fazekas, Franz
Abstract : Background and Purpose—: Cerebral amyloid angiopathy–related cortical superficial siderosis (cSS) seems to indicate an increased risk of subsequent intracerebral hemorrhage (ICH). We wanted to identify the mechanisms and sequence of hemorrhagic events which are responsible for this association. Methods—: During a 9-year-period, we identified patients with spontaneous convexal subarachnoid hemorrhage (cSAH) and performed a careful longitudinal analysis of clinical and neuroimaging data. A close imaging–histopathologic correlation was performed in one patient. Results—: Of 38 cSAH patients (mean age, 77±11 years), 29 (76%) had imaging features of cerebral amyloid angiopathy on baseline magnetic resonance imaging. Twenty-six (68%) had cSS. Sixteen subjects underwent postcontrast magnetic resonance imaging. Extravasation of gadolinium at the site of the acute cSAH was seen on all postcontrast scans. After a mean of 24±22 (range 1–78) months of follow-up, 15 (39%) had experienced recurrent cSAHs and 14 (37%) had suffered lobar ICHs. Of 22 new ICHs, 17 occurred at sites of previous cSAHs or cSS. Repeated neuroimaging showed expansion of cSAH into the brain parenchyma and evolution of a lobar ICH in 4 patients. Propagation of cSS was observed in 21 (55%) patients, with 14 of those having experienced recurrent cSAHs. In the autopsy case, leakage of meningeal vessels affected by cerebral amyloid angiopathy was noted. Conclusions—: In cerebral amyloid angiopathy, leakage of meningeal vessels seems to be a major cause for recurrent intrasulcal bleedings, which lead to the propagation of cSS and indicate sites with increased vulnerability for future ICH. Intracerebral bleedings may also develop directly from or in extension of a cSAH. Abstract : Supplemental Digital Content is available in the text.